2003
DOI: 10.1167/iovs.02-0171
|View full text |Cite
|
Sign up to set email alerts
|

Strabological Findings after Macular Translocation Surgery with 360° Retinotomy

Abstract: Adaptive mechanisms are activated to reduce the surgically induced objective angle of cyclotorsion, and a cyclodeviation of 15 degrees was the critical angle separating those who had peripheral fusion from those who did not. This value corresponds to the cyclofusional amplitude in normal adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 19 publications
2
18
0
Order By: Relevance
“…Infants may have an extremely large fusional potential compared to that of adults. [6][7][8] The critical period and amplitude of infantile fusional potential remain uncertain; however, these cases may suggest that a positive prognosis is possible after macular rotation surgery in infants.…”
Section: Discussionmentioning
confidence: 99%
“…Infants may have an extremely large fusional potential compared to that of adults. [6][7][8] The critical period and amplitude of infantile fusional potential remain uncertain; however, these cases may suggest that a positive prognosis is possible after macular rotation surgery in infants.…”
Section: Discussionmentioning
confidence: 99%
“…A small number of patients have been reported to have binocular single vision after MT360 and counterrotation surgery. However, the majority of patients suppress the operated or fellow eye [12]. Residual cyclotorsion or simple misalignment of the visual axes between the two eyes cannot be held solely responsible for the lack of binocular single vision because factors such as poor visual acuity, non-corresponding retinal points outside of Panum's fusion area and retinally induced aniseikonia might also play a contributory role.…”
Section: Discussionmentioning
confidence: 99%
“…Fifteen patients ignored the second image and 12 developed diplopia. 20 In another study by Gelisken, 20% of patients suffered from diplopia, 21 whereas Abdel-Meguid reported 46% with persistent diplopia. 22…”
Section: Incidencementioning
confidence: 98%